Heat Source in a Pyrolysis Reactor Design for Energy Converting of Polypropylene into Fuel Oil at PPSDM Migas, Cepu - Mulyono, Mulyono; Roihatin, Anis; Mukti, Reka Handoyo; Aulia, Nur Fatowil; Huda, Luqman Al (Eksergi, 2025)
Furnace-02 at PPSDM Migas is utilised in the petroleum processing of residual fuel. The efficiency value of furnace-02 is 62.71%, with 119,1763 Btu/h of heat being wasted through flue gas and a flow velocity of 164 m3/min. The heat value in the flue gas is utilised for the purpose of pyrolysis of the plastic, with a view to optimising energy use in the furnace. The process of plastic pyrolysis has been demonstrated to yield pyrolysis oil, which possesses a calorific value comparable to that of gasoline (10,520 kcal/kg). This pyrolysis oil has the potential to serve as a substitute fuel source for fossil fuels. The design of the pyrolysis system burner modification is such that its capacity is 75 kg/hour. The energy utilisation in the design amounted to 28,645.02 kJ/h, representing 2.3% of the total flue gas heat.